Pengaruh Media Interaktif Berbasis Powerpoint Berbantuan Ispring Suite 10 Terhadap Hasil Belajar Siswa pada Materi Energi Kelas IV SD Negeri 14 Simpang Teritip - Riska Anggraini; Feri Ardiansah; Hevitria (JBES (Journal Basic Education Skills), 2026)
This study was motivated by the low learning outcomes of fourth-grade students at SDN 14 Simpang Teritip in the Natural and Social Sciences (IPAS) subject. The underutilization of interactive learning resources, which frequently results in students becoming disinterested and less engaged, is one of the contributing factors. This study's goal was to ascertain the impact of PowerPoint-based interactive media assisted by iSpring Suite 10 on students’ learning outcomes. The study used a quantitative method with a quasi-experimental design. each with 20 students. The research instrument was a learning achievement test in the form of pretest and posttest, which through normality, homogeneity, and hypothesis testing. The data were normally distributed (Shapiro-Wilk Sig. > 0.05) and had homogeneous variance (Levene Test Sig. = 0.749). Hypothesis testing using Independent Samples T-Test was then carried out. The test results showed a t-count value of 6.143 with a two-tailed significance value (Sig. (2-tailed) of 0.000. The mean of the experimental group and the control group learning results differ statistically significantly, as indicated by the significance value of 0.000, which is significantly less than alpha = 0.05. Thus, the Ha was accepted, concluding that theeuse of PowerPoint-based interactive media assisted by ispring Suite 10 Had a big impact on helping fourth-grade students learn better about energy topics. These results confirm the effectiveness of interactive media as a learning innovation in elementary schools.